"أثر الخدمات اللوجستية في تنافسية الصادرات السلعية دراسة حالة الإمارات العربية المتحدة للفترة 2007-2021 " - جعفر, اعبيد; اكرم, حاج عمار; غربي, عبد الحق (unuversity of eloued- جامعة الوادي, 2023)
تحاول هذه الدراسة قياس أثر الخدمات اللوجستية المتمثلة في مؤشر الأداء اللوجستي ومؤشر ربط الشحن البحري، في تنافسية الصادرات السلعية، وقد تم الاعتماد على مؤشر التنويع للصادرات، من خلال بيانات سنوية خلال الفترة الزمنية (2007-2021) لدولة الامارات العربية المتحدة، ولتحقيق ذلك استخدمت الدراسة الانحدار المتعدد باستخدام طريقة المربعات الصغرى العادية وبالاستعانة ببرنامج 12 EVIEWS. خلصت النتائج الى أن تحسن الخدمات اللوجستية من خلال مؤشر الأداء اللوجستي ومؤشر ربط الشحن البحري يؤثر ايجابا على تنافسية الصادرات في الامارات، أما باقي المتغيرات المستقلة الأخرى فهناك أثر سلبي للتضخم على تنافسية الصادرات، في حين عدم وجود أثر لنمو نصيب الفرد من الناتج المحلي على تنافسية الصادرات، واما الاستثمار الأجنبي المباشر فله أثر ايجابي على تنافسية الصادرات لدولة الامارات. This study attempts to measure the impact of logistics services, represented by the logistic performance index and the maritime freight linkage index, on the competitiveness of commodity exports. The export diversification index has been relied upon, through annual data during the time period (2007-2021) for the United Arab Emirates. The study is a multiple regression using the method of ordinary least squares and using the program 12 EVIEWS. The results concluded that the improvement of logistical services through the logistic performance index and the maritime freight linkage index positively affects the competitiveness of exports in the UAE. As for the rest of the other independent variables, there is a negative effect of inflation on the competitiveness of exports, while there is no effect of the growth of per capita GDP on the competitiveness of exports. Exports. As for foreign direct investment, it has a positive impact on the competitiveness of exports to the UAE.
Keywords: خدمات لوجستية، تنافسية الصادرات مؤشر تنويع الصادرات، الامارات العربية المتحدة، طريقة المربعات الصغرى العادية.; logistics services, export competitiveness, export diversification index, United Arab Emirates, ordinary least squares method.